Cytotoxic Compounds from the Fruits of Uapaca togoensis towards Multifactorial Drug-Resistant Cancer Cells - Kuete, Victor; Sandjo, Louis P.; Seukep, Jackson A.; Zeino, Maen; Mbaveng, Armelle T.; Ngadjui, Bonaventure; Efferth, Thomas (Planta Medica, 2015)
Cancer cells may rapidly acquire multidrug resistance, mainly due to the presence of adenosine triphosphate-binding cassette transporters, epidermal growth factor receptor, or mutations in the p53 tumor suppressor gene. This work was designed to assess the cytotoxicity of the methanol crude extracts and compounds from the fruits of Uapaca togoensis, namely, β-amyryl acetate (1), 11-oxo-α-amyryl acetate (2), lupeol (3), pomolic acid (4), futokadsurin B (5), arborinin (6), and 3-O-β-D-glucopyranosyl sitosterol (7) against nine drug sensitive and multidrug-resistant cancer cell lines. The resazurin reduction assay was used to evaluate the cytotoxicity of the fruits of U. togoensis and compounds, whilst the caspase-Glo assay was used to detect the activation of caspase enzymes by the fruits of U. togoensis and compound 6. Cell cycle, mitochondrial membrane potential, and levels of reactive oxygen species were all analyzed via flow cytometry. The acridone alkoid 6 and the crude extract from the fruits of U. togoensis were active on all of the nine tested cancer lines with IC50 values below 32 µM and 30 µg/mL, respectively. Compounds 2 and 5 showed selective activities and IC50 values below 99 µM or 42 µM, respectively, which were obtained towards 3/9 and 6/9 tested cancer cell lines. Compound 6 displayed IC50 values below 10 µM towards seven of the nine tested cancer cell lines. The IC50 values ranged from 3.55 µM (against CEM/ADR5000 cells) to 31.77 µM (against CCRF-CEM cells) for alkaloid 6 and from 0.20 µM (against CCRF-CEM cells) to 195.12 µM (against CEM/ADR5000 cells) for doxorubicin. The crude extract of the fruits of U. togoensis induced apoptosis in the CCRF-CEM leukemia cells, which was mediated by the disruption of the mitochondrial membrane potential. Compound 6 also strongly induced apoptosis in CCRF-CEM cells and cell cycle arrest in the G0/G1 and S phases. The crude extract from the fruits of this plant as well as aborinin are potential antiproliferative natural products that deserve further investigation to develop novel cytotoxic drugs to fight sensitive and otherwise drug-resistant phenotypes.
Keywords: Uapaca togoensis; Euphorbiaceae; alkaloid; arborinine; cytotoxicity; apoptosis